2005
DOI: 10.1002/mus.20315
|View full text |Cite
|
Sign up to set email alerts
|

TSH receptor protein is selectively expressed in normal human extraocular muscle

Abstract: Thyroid-associated ophthalmopathy is a common manifestation of Graves' disease. Its pathophysiology is not well understood but an antigen shared between the thyroid and orbit is thought to play a role. Using immunohistochemistry, we have demonstrated the presence of the autoantigenic target of Graves' disease, the thyroid-stimulating hormone receptor, in normal human extraocular muscle. These results support previous findings of the full length and splice variant thyroid-stimulating hormone receptor cDNA in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…However, TSH-R was expressed in a similar amount compared to the expression level in mouse hypothalamic tissue, where TSH-R is reported to be present [12]. Also, we confirmed that the PCR bands were the true TSH-R using a direct sequencing method after DNA extraction from the expected bands.…”
Section: Discussionsupporting
confidence: 75%
“…However, TSH-R was expressed in a similar amount compared to the expression level in mouse hypothalamic tissue, where TSH-R is reported to be present [12]. Also, we confirmed that the PCR bands were the true TSH-R using a direct sequencing method after DNA extraction from the expected bands.…”
Section: Discussionsupporting
confidence: 75%
“…A remaining central question concerns the identity of the primary autoimmune target in TAO. Extraocular muscle has been proposed by a few investigators, [92][93][94][95][96][97] but most have focused on orbital fibroblasts. 98 Supporting the latter point of view, infiltrating CD8 þ T cells recognize orbital fibroblasts, and become activated through MHC class II and CD40-dependent signaling, 7 suggesting that these cells represent autoimmune targets.…”
Section: Orbital Fibroblasts and The Putative Role Of Bone Marrow-dermentioning
confidence: 99%
“…In general, the evidence for TSHR in extraocular muscle is less abundant than the data demonstrating TSHR in adipose tissue. The selective expression of TSHR in extraocular muscle reported by Kloprogge et al (2005) contrasts with the more widespread nature of TSHR expression in various GD fat depots . The extraocular muscle enlargement in GO has previously been considered to be the result of inflammation and oedema rather than hyperplasia or hypertrophy of the myocytes themselves (Hufnagel et al 1987).…”
Section: Tshr and Musclementioning
confidence: 75%